Assessment of knowledge of ergonomics among preclinical undergraduate students: A cross-sectional study - Chetana Rambhad; Neelam Pande; Usha Radke (Wolters Kluwer Medknow Publications, 2018)
Background: As there is an increase in issue identified as musculoskeletal disorders (MSDs) in the field of dentistry, dental specialists are unconscious of this until the point when they encounter. Hence, it should be included in the curriculum of preclinical undergraduate students to make them aware and to adopt preventive measures to avoid them. Aim: The aim of the present study was to assess the knowledge of ergonomics in preclinical undergraduate students. Materials and Methods: The study conducted was questionnaire based with 100 participants, who are BDS II-year students performing prosthodontics preclinical exercises. The participant was approached through a printed questionnaire which included the purpose of the study followed by informed consent. Results: Our study revealed that students were experiencing pain and discomfort during preclinical exercises. And, they were aware of the fact that it was due to incorrect working postures. However, they did not know the precautionary measures to be taken to avoid this problem, and they were keen in learning the correct working measures. Eighty-five percent of students thought that it should be included in the curriculum, and professors should decide the same. Conclusion: There is a strong relation between the incorrect working posture and the MSDs. As 51% of students experienced pain and discomfort during preclinical classes in our study, it is necessary to include the knowledge of ergonomics in the curriculum and practice of the same.